Plasticity of Membrane Binding by the Central Region of α-Synuclein - Navarro-Paya, Carlos; Sanz-Hernandez, Maximo; De Simone, Alfonso (Frontiers in Molecular Biosciences, 2022)
The membrane binding by α-synuclein (αS), an intrinsically disordered protein whose aggregation is associated with Parkinson’s disease, is a key step to determine its biological properties under both physiological and pathological conditions. Upon membrane binding, αS retains a partial level of structural disorder despite acquiring α-helical content. In the membrane-bound state, the equilibrium between helical-bound and disordered-detached states of the central region of αS (residues 65-97) has been involved in a double-anchor mechanism enabling to promote the clustering of synaptic vesicles. Here we investigated the underlying molecular bases of this equilibrium by using enhanced coarse-grained MD simulations. The results enabled to clarify the conformational dependencies of the membrane affinity by this protein region that, in addition to playing a role in physiological membrane binding, has key relevance for the aggregation of αS and the mechanisms of toxicity of the resulting assemblies.